Entrepreneurial orientation: The necessity of a multilevel conceptualization - Wales, William J.; Covin, Jeffrey G.; Monsen, Erik (Strategic Entrepreneurship Journal, 2020)
Research Summary An original and clarifying conceptualization of entrepreneurial orientation (EO) is advanced based upon three fundamental ways in which entrepreneurship can be manifest as an organizational attribute: as top management style, organizational configuration, and new entry initiatives. We leverage this conceptualization to examine the presumed state of irreconcilable differences between the Miller (1983)/Covin and Slevin (1989) and Lumpkin and Dess (1996) conceptualizations of EO. This research proposes that these conceptualizations are reconcilable when the problem is reframed to consider how EO is manifest as an organizational attribute at and across multiple levels of analysis. Like the blind men and the elephant, these works have drawn attention to different aspects of a broader phenomenon. How EO as a multifaceted organizational attribute shapes future scholarly dialogue is discussed. Managerial Summary The concept of entrepreneurial orientation (EO) has been proposed as a way of envisioning what it means for organizations to “be entrepreneurial.” There is more than one answer to this question. This paper describes three principal ways entrepreneurship‐as‐an‐organizational attribute has been discussed, including illustrative examples from real‐world businesses. One perspective recognizes the entrepreneurial aspect of organizations by considering top management style; a second perspective recognizes that organizations manifest entrepreneurship through a configuration of key organizational elements; and a third perspective looks to evidence of the organization's entry into new offerings and domains of operation as indicative of entrepreneurship. All three manifestations of “being entrepreneurial” are part of the current conversation on EO. This paper recognizes the conceptual legitimacy and practical interdependence of these distinct perspectives.